Designing Child-Friendly Digital Comics Integrating Local Wisdom and PBL-SSI for Environmental Disaster Learning Materials in Primary Schools - Ika Ari Pratiwi; Eko Handoyo; Isti Hidayah (Proceedings of International Conference on Science, Education, and Technology, 2026)
The principle of child-friendly learning emphasizes the importance of providing safe, meaningful, participatory learning experiences that are appropriate to the developmental characteristics of students. However, the learning of science and science in grade IV of primary schools on environmental disaster material encountered obstacles in connecting science concepts with real problems experienced by students. The researchers also found non-optimally utilized digital media that integrated local wisdom. This study analyzed the learning needs of environmental disaster material reviewed from the aspect of media and integration of child-friendly local wisdom; design a child-friendly digital comic that integrates local wisdom and PBL-SSI in disaster material; and identify the characteristics of digital comics that support science and science learning. This Research and Development (R&D) method used the ADDIE model limited to the Analysis and Design stages. The researchers collected through observation, interviews, and document analysis, then analyzed using thematic analysis. The results of the study indicate the need for contextual, interactive, and close-to-student experience learning media. Based on these needs, the researchers designed the digital comic “Pahlawan Lingkungan dari Kesambi”, integrating local wisdom, child-friendly principles, PBL-SSI, QR Code, and Heyzine flipbook. The resulting comic has eight key characteristics that support environmental awareness and critical thinking. This research contributes to the development of a child-friendly digital comic design framework based on local wisdom and PBL-SSI for environmental disaster learning in primary schools.